2008
DOI: 10.1197/jamia.m2532
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of a Clinician Reporting System for Advanced Stage Cancer: Initial Lessons Learned

Abstract: Though in its early implementation stages, the CR demonstrates the potential to positively impact care delivery in the cancer clinic setting, particularly by facilitating earlier interventions and improving patient-caregiver-clinician communication both during and between clinic visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 46 publications
1
52
0
2
Order By: Relevance
“…64 Some clinicians indicated that the assessed symptoms were already frequently monitored at clinic visits, therefore limiting the usefulness of the CR. Accordingly, systems need to be designed around the needs of those they plan to serve, offering functionality that clearly fulfills a need.…”
Section: Case Example: Chessmentioning
confidence: 99%
“…64 Some clinicians indicated that the assessed symptoms were already frequently monitored at clinic visits, therefore limiting the usefulness of the CR. Accordingly, systems need to be designed around the needs of those they plan to serve, offering functionality that clearly fulfills a need.…”
Section: Case Example: Chessmentioning
confidence: 99%
“…CHESS is distinguished by the quality and depth of its information and resources and by ease of use. CHESS is an extensively studied eHealth system, having been (over its evolutions) the subject of numerous needs assessments (DuBenske et al, 2008a; DuBenske et al, 2008b; Wen & Gustafson, 2004) randomized clinical trials (Gustafson et al, 2001, 2008), and field tests (Gustafson et al, 2005; Gustafson, McTavish, Schubert, & Johnson, 2012). These studies demonstrated that CHESS can be widely accepted and used, improve patient quality of life and information competence, and in some cases lead to more efficient use of health services (Gustafson et al, 2001; Shaw et al, 2007; Shaw, McTavish, Hawkins, Gustafson, & Pingree, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study done at a palliative unit where an electronic assessment tool was being implemented reported perceived difficulties related to establishing new routines, increased workload, technology issues, increased burden for patients, and ethical issues due to concerns about whether or not the system would actually benefit the patients [21]. Functional and technological issues, the users' desire for more in-depth information, user privacy concerns, and limited patient use are other challenges noted when implementing new systems in clinical practice [23]. However, while a number of studies have addressed aspects of system implementation, less research has examined the challenges that may emerge over time or the impact of new interventions after they have been implemented [24].…”
Section: The Choice Applicationmentioning
confidence: 99%